7th Grade Students’ Perceptions of Zep Quiz for Gamified Vocabulary Learning - Rini Musrifa; Ida Ayu Panuntun (Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery often becomes a hurdle for junior high school students, particularly when the teaching methods lack variety. This study aims to describe the learning problems faced by seventh-grade students, the implementation process, and their perceptions toward the use of Zep Quiz as a gamification media in vocabulary learning. A descriptive qualitative approach was employed, involving 38 seventh-grade students as the sample, with five students selected for interviews. Data were collected through questionnaires, semi-structured interviews, vocabulary tests, and documentation. Questionnaire data were analyzed descriptively, while interview data were analyzed using thematic analysis based on Miles and Huberman's interactive model. The findings revealed that students primarily struggled with remembering new words and using them in proper contexts. The teacher implemented Zep Quiz as a supplementary tool for practice and assessment, which ran interactively in the classroom. Overall, students held positive perceptions. They felt more motivated, more active, and found the learning process enjoyable. The average vocabulary test score reached the high category. Nevertheless, some students reported technical issues such as unstable internet connections, and a few felt pressured by the point system and time limits. Additionally, several students still relied on traditional memorization strategies for long-term vocabulary retention. This study recommends integrating Zep Quiz as a complement to, rather than a replacement for, conventional teaching methods.